2015
DOI: 10.1177/1933719115592711
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Investigation of Metastasis-Related Chemokines in Deep-Infiltrating Endometriosis and Compromised Pelvic Sentinel Lymph Nodes

Abstract: Endometriosis is a prevalent benign disease, despite sharing several similarities with malignancies, such as the possibility of lymphatic spread. In malignancies, chemokines play a sovereign role in the process of metastasis. Metastasis-related chemokine axes have not yet been assessed in deep-infiltrating endometriosis (DIE), and this investigation was the aim of our study. The expression of these chemokines was investigated by immunohistochemistry in rectovaginal DIE lesions and in matched pelvic sentinel ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
(68 reference statements)
0
8
0
2
Order By: Relevance
“…The lymphatic spread of endometriosis, connected to the hyper expression of two chemokine receptors, also involved in the process of metastasis in cancer, CCR7 and CXCR4 [33] could hypothetically create a microembolus, able to obstruct the course of the lymphatic flow. However, at the moment, these are only hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphatic spread of endometriosis, connected to the hyper expression of two chemokine receptors, also involved in the process of metastasis in cancer, CCR7 and CXCR4 [33] could hypothetically create a microembolus, able to obstruct the course of the lymphatic flow. However, at the moment, these are only hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Although endometriosis is a benign, estrogen‐dependent disease, endometriotic cells share some features with cancer cells, such as invasiveness and the potential to metastasize . Therefore, the establishment and development of endometriosis is thought to share several mechanisms, including epithelial‐mesenchymal transition (EMT), with malignant disorders .…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of EMS is unclear, the reflux theory of menstruation is most widely accepted. It is suggested that invasion and metastasis is a very important step in flowing endometrial tissue ( Borrelli et al, 2015 ; Chui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%